Effect of Single and Multiple Lasers on Microstructure and Porosity of AlSi10Mg Parts Produced by Laser Powder Bed Fusion with Different Process Parameters - Coşkun, Mert; Sağbaş, Binnur (Sage, 2025)
Laser powder bed fusion (L-PBF) is a rapidly developing additive manufacturing method that builds parts layer by layer by melting them via a laser beam. It provides the opportunity to generate complex and custom geometries. However, the L-PBF process must still be suitable for mass production due to its relatively slow build rate, high production costs, and limited scalability. The single-laser systems commonly used in L-PBF restrict the build speed, as only a single laser can operate in a specific area at a time. Multi-laser systems are being developed to accelerate the process. However, challenges remain, such as ensuring that the lasers do not interfere with each other and maintaining consistent build quality across the entire part geometry. This study examines the physical and microstructural properties of the samples produced in single and multiple lasers with standard and different process parameters by L-PBF. Optical, digital microscopes and X-ray micro-computed tomography (micro-X CT) were used to analyse the samples. The hatch distance and scanning parameters strategy have been observed to affect the sample properties produced significantly, regardless of single or multiple lasers. Micro-X CT and density results confirm each other. It can be concluded from the results that using multiple lasers can be a promising solution to the serial production of critical parts that were previously manufactured by single-laser systems, as it does not negatively affect density and microstructure.
Keywords: Laser Powder Bed Fusion; Process Parameters; Microstructure; X-ray Micro-Computed Tomography; Multiple Lasers